2021
DOI: 10.1093/sleep/zsab139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the menopausal transition on polysomnographic sleep characteristics: a longitudinal analysis

Abstract: Study Objectives To evaluate how change in menopausal status related to spectral analysis and polysomnographic measures of sleep characteristics. Methods The Study of Women’s Health Across the Nation (SWAN) Ancillary Sleep Study evaluated sleep characteristics of 159 women who were initially pre- or early perimenopausal and repeated the assessment about 3 ½ years later when 38 were pre- or early perimenopausal, 31 late perime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Furthermore, these results were confirmed in later studies of polysomnographic sleep in a subgroup of SWAN participants [39]. In fact, in this study increased beta-EEG power in NREM sleep was shown in women transitioning to post-menopause, suggesting that the menopausal transition is associated with physiological overexcitation during sleep independent of self-reported hot flashes [39]. A relationship between sleep changes and cortisol with ageing has been reported [41,42].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, these results were confirmed in later studies of polysomnographic sleep in a subgroup of SWAN participants [39]. In fact, in this study increased beta-EEG power in NREM sleep was shown in women transitioning to post-menopause, suggesting that the menopausal transition is associated with physiological overexcitation during sleep independent of self-reported hot flashes [39]. A relationship between sleep changes and cortisol with ageing has been reported [41,42].…”
Section: Discussionsupporting
confidence: 84%
“…Studies of sleep quality during the menopausal transition and post-menopause revealed that lower estradiol levels were associated with night-time awakening [38]. Findings from the Study of Women's Health Across the Nation [39] indicated that lower estradiol levels and higher FSH were associated with difficulty falling asleep and remaining asleep [40]. Furthermore, these results were confirmed in later studies of polysomnographic sleep in a subgroup of SWAN participants [39].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Consistent with these data, Gomez Santos et al found that postmenopausal women slept 10% fewer hours than premenopausal women [5]. Studies of sleep quality during the menopausal transition and after menopause found that lower estradiol levels were associated with nocturnal awakenings [24,57]. Results from the Study of Women's Health Across the Nation (SWAN) indicated that lower estradiol levels and higher FSH were associated with difficulty falling asleep and staying asleep [24].…”
Section: Chronotype and Menopausementioning
confidence: 90%
“…Further, compared to estradiol therapy alone, combined estradiol and various progesterone and progestin therapies produced greater improvements in sleep quality in postmenopausal women (Montplaisir et al, 2001 ; Saletu, 2003 ; Gambacciani et al, 2005 ). Though results of HRT trials suggest that HRT increases SWS, longitudinal observational studies have shown increases in SWS sleep in postmenopausal women not taking HRT, while other metrics suggest that HRT increases wakefulness after sleep onset and sleep fragmentation (Lampio et al, 2017 ; Kalleinen et al, 2021 ; Matthews et al, 2021 ). Further, in one study, postmenopausal and perimenopausal women subjectively reported more sleep complaints than premenopausal women, yet obtained more SWS (Young et al, 2003 ).…”
Section: Interrelationships Among Female Sex Hormones Sleep and Memor...mentioning
confidence: 99%